Pelatihan Perhitungan Harga Pokok Penjualan Untuk Penentuan Harga Jual Barang Dagang dan Barang Produksi UMKM - Mufarokhah, Nur; Khasanah, Uswatun; Zainab, Zainab; Vitriya, Rezza; Rahmah, Yulia (Jurnal ABM Mengabdi, 2025)
This Community Service activity aims to increase the knowledge of Micro, Small and Medium Enterprises (MSMEs) in determining the selling price of Merchandise and Goods produced. This activity was carried out in Morobakung village, Manyar District, Gresik Regency to improve the economy of MSMEs. This Service Method is carried out through Counseling and Training by inviting MSME actors in Morobakung Village. Determining the selling price is very important for MSMEs because it will cause profits that cannot be calculated according to the circumstances. Therefore, this Cost of Goods Sold Counseling is carried out to provide understanding to MSME Actors in determining what costs are calculated and charged in a product sold and produced